Behaviorism and the concepts of influencing the attitudes of patients towards health behaviors - Artur Prusaczyk; Joanna Oberska; Paweł Żuk; Marika Guzek; Bogdan Magdalena (Kazimierz Wielki University, 2023)
Health professionals in primary care teams need to know how to effectively encourage patients to change health behaviors to achieve treatment goals. Understanding the behavioral patterns and psychological underpinnings of making changes can help healthcare professionals deliver interventions with a higher success rate. The aim of the study was to assess the importance of behavior patterns in shaping patients' health attitudes and behaviors. There are three types of theoretical models that explain how health behaviors are initiated and changed: motivational, post-intentional, and multistage models. Motivation models describe the role of individual cognitive variables in the process of creating the intention to change behavior. Changing habits in the context of health promotion takes place by influencing the perception of patients. This can be achieved using the TRA (Theory of Reasoned Action), TBP (Theory of Planned Behavior) and HBM (Health Belief Model) models by convincing the public about susceptibility to a given disease, disseminating knowledge about effective methods of prevention and generating persuasion, support, admiration or recognition in society after positive behaviors such as smoking cessation or regular physical activity. Post-intentional models indicate factors that increase the chance of translating motivation into action. They commit the individual to a certain action when certain environmental circumstances are met, thus helping to translate the intention of the goal into action. Multi-stage models describe health behaviors as involving several separate stages. These theories are based on the assumption that people at different stages will behave differently, so the types of interventions and information needed to change behavior will vary depending on the stage they are at. Helping patients set realistic goals, such as moving to the next stage, can facilitate the change process. Effective behavioral interventions must be based on changing the approach of medical staff to the interpersonal process with the patient. This approach should be patient-centred and collaborative. Medical staff should assess the importance that the patient attaches to his health and the treatment process, and thus also the willingness and motivation to comply with the recommendations. Merely providing information will not guarantee a change in their behavior. Healthcare professionals should use active listening techniques (using open-ended questions, explanations, reflective and summarizing statements), should encourage patients to express concerns, and should be able to weigh the pros and cons of different treatment approaches.